Applying S88 Batch Control from a User's Perspective. - Parshall, Jim H.; Lamb, Larry B. (ISA, 1999)
Annotation Process automation engineer Parshall and software manager Lamb were charged with implementing a more flexible batch control system at a well know ice cream producer. They focus on the ISA S88.01 standard, and here pass on what they learned as an example of how to understand, justify, and implement the standard in a wide range of process industries. The price for members is $20. Annotation copyrighted by Book News, Inc., Portland, OR.
Keywords: elektronické knihy; electronic books